Catalytic filter bag for removal of fine particles in incineration flue gas and catalytic oxidation of VOCs (volatile organic compounds) as well as preparation method and application of catalytic filter bag

By adopting CoO-MnO-In2O3@TiO2 core-shell structure catalyst and automatic spraying technology, the existing oxidation catalysts have been solved, and the activity of low-temperature oxidation catalysts is insufficient, efficient fine particulate removal and VOCs catalytic oxidation effects are achieved, and the sulfur resistance and thermal stability of the catalyst are improved.

CN119548903AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411779591.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing oxidation catalyst has high operating temperature, and the medium and low temperature oxidation catalysts have defects such as low temperature activity, anti-sulfur poisoning ability and thermal stability. The combination strength of the catalyst and the filter material is not high, resulting in the removal of fine particulate matter and the low oxidation efficiency of VOCs.

Method used

CoO-MnO-In2O3@TiO2 core-shell structure catalyst is used to combine CoO-MnO-In2O3 and TiO2 through the preparation method to form a catalyst with high activity, and the production efficiency of the catalytic filter bag is improved through automatic spraying technology.

Benefits of technology

The catalytic oxidation and removal efficiency of VOCs is significantly improved at lower temperatures, the sulfur resistance and thermal stability of the catalyst are enhanced, the bonding strength and loading rate between the catalyst and the filter material are improved, and the life of the catalyst is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a catalytic filter bag for incineration flue gas fine particle removal and VOCs catalytic oxidation as well as a preparation method and application of the catalytic filter bag, and belongs to the technical field of waste incineration flue gas purification. The method comprises the following steps: grinding CoO-MnO-In2O3-coated TiO2 and an auxiliary agent, uniformly mixing, sequentially adding water and nitric acid, and uniformly mixing, so as to obtain a matrix supported catalyst sol slurry; and spraying the matrix supported catalyst sol slurry on the pretreated filter bag carrier, and sequentially drying and roasting to obtain the catalytic filter material. The formed catalyst sol slurry has higher adhesiveness with a filter bag matrix and higher load rate; and an automatic spraying technology is adopted, so that the production efficiency of the catalytic filter bag is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waste incineration flue gas purification, and specifically relates to a catalytic filter bag used for removing fine particles from incineration flue gas and catalytic oxidation of VOCs, and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are one of the main air pollutants, which are seriously harmful to human health and the ecological environment. Industrial sources are the largest source of VOCs pollution, with the characteristics of high emission intensity, high emission concentration, complex emission components and long duration. Catalytic oxidation is the process of decomposing toxic and harmful VOCs into non-toxic CO2 and H2O under certain reaction conditions using catalysts. It has the advantages of mild reaction conditions, good safety and high conversion efficiency. It is one of the most efficient technologies for VOCs treatment at present, and high-efficiency oxidation catalysts are the core of VOCs catalytic oxidation technology. At present, the operating temperature of commercial VOCs catalysts is usually above 350℃, which is difficult to adapt to occasions with low exhaust temperature; medium and low temperature oxidation catalysts need to be improved in low temperature activity, sulfur poisoning resistance and thermal stability. On the other hand, a large amount of dust is also emitted in industrial flue gas. The coexistence of multiple pollutants requires the use of multi-step removal and treatment technical means, resulting in large equipment footprint, high treatment cost and complex operation. The use of fine particle filtration and VOCs catalytic oxidation filter bag technology can effectively solve this problem.

[0003] Patent CN 109954403 A discloses a plasma-coordinated catalyst-oxidative degradation of VOCs dust filter cloth, which is woven alternately by warp and weft yarns in conventional plain, twill or satin forms. The dust filter cloth is powered on during dust removal operation, and the conductive yarn on the filter bag electrolyzes the air to prepare plasma, which cooperates with a catalyst selected from the CuO-ZnO-MgO-Al2O3 mixture, copper-manganese-cerium composite metal oxide, Cu-Al2O3, CuO-Mn2O4 composite metal oxide, AgO-Mn2O4 composite metal oxide, and Co3O4-Ce O2 composite metal oxide co-loaded on the filter bag to efficiently degrade gaseous volatile organic compounds in the exhaust gas. CN 107321348B discloses a catalytic fiber capable of catalytically removing organic gaseous pollutants, a preparation method thereof, a catalytic filter bag and a bag filter, wherein the catalytic fiber comprises a PTFE fiber substrate and a catalyst which is expanded and melted and filled in the PTFE fiber substrate, and the catalyst comprises titanium dioxide as a catalyst carrier and one or more activators selected from vanadium pentoxide, platinum and palladium and one or two antioxidants selected from tungsten trioxide and molybdenum trioxide which are composited on the catalyst carrier.

[0004] The main problems in the existing technology are as follows: first, the operating temperature of conventional oxidation catalysts is high; second, medium and low temperature oxidation catalysts have defects in low temperature activity, sulfur resistance and thermal stability; third, the bonding strength between the catalyst and the filter material is not high, and the removal efficiency of fine particles and VOCs oxidation is relatively low. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides a catalytic filter bag for removing fine particles from incineration flue gas and catalytic oxidation of VOCs, as well as a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a catalytic filter bag, the method comprising the following steps:

[0008] (1) dodecylamine and alcohol are added to deionized water to form a microemulsion liquid, cobalt salt, manganese salt and indium salt are added to the microemulsion liquid and mixed; after mixing, the mixture is slowly added to a precipitant, and then stirred for 12 to 20 hours. The obtained crystals are sequentially subjected to standing, centrifugation, washing, drying, roasting and grinding to obtain a CoO-MnO-In2O3 ternary metal oxide composition with a particle size of 5 to 15 μm;

[0009] (2) Adding a CoO-MnO-In2O3 ternary metal oxide composition to an alcohol aqueous solution and dispersing it uniformly, then adding TiCl4 and reacting it at a temperature of 75 to 85°C for 1.5 to 2 hours, then drying the gel and calcining it to obtain a CoO-MnO-In2O3@TiO2 catalyst composition having a core-shell structure;

[0010] (3) Grinding and mixing CoO-MnO-In2O3@TiO2 and the additive, and then sequentially adding water and nitric acid and mixing, to obtain a matrix-supported catalyst sol slurry;

[0011] (4) The substrate-loaded catalyst sol slurry is sprayed onto the pretreated filter bag carrier and then dried and calcined in sequence to obtain a catalytic filter material.

[0012] In the above preparation method, the alcohol in step (1) is n-butanol, and the mass ratio of dodecylamine, n-butanol and deionized water in the microemulsion is 1-5:8-12:10-20;

[0013] The mass ratio of the microemulsion to the metal salt is 20-30:1-5, and the metal salt is cobalt salt, manganese salt and indium salt.

[0014] In the above preparation method, the drying temperature in step (1) is 120-150°C, the drying time is 4-8 hours, the roasting temperature is 550-650°C, and the roasting time is 4-10 hours;

[0015] The precipitant is a mixed solution of sodium hydroxide and sodium carbonate, and the molar ratio of the sodium hydroxide to ammonium carbonate is 1-3:1-3.

[0016] In the above preparation method, the alcohol aqueous solution described in step (2) is a 40-60% ethanol solution; the drying temperature is 100-130° C., and the drying time is 12-20 hours; the roasting temperature is first roasted at a temperature of 400-450° C. for 2-4 hours, and then roasted at 630-680° C. for 4-8 hours.

[0017] In the above preparation method, the mass concentration of the substrate-supported catalyst sol slurry in step (3) is 1 to 10%.

[0018] In the above preparation method, the auxiliary agent described in step (3) is a combination of SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder in a mass ratio of 3-15:0.1-1, and the mass ratio of the auxiliary agent and the CoO-MnO-In2O3@TiO2 catalyst composition is 1-3:1-3.

[0019] In the above preparation method, the filter bag pretreatment method in step (4) is to soak it in 10-30% nitric acid at a temperature of 40-50°C for 1-3 hours, then wash it and dry it at 100-110°C for 1-3 hours; the material used for the filter bag is tetrafluoroethylene PTFE, polyphenylene sulfide PPS or polyimide P84.

[0020] In step (4), the drying temperature is 105-120° C. for 3-6 hours, and the calcination temperature is 180-220° C. for 1-8 hours.

[0021] A catalytic filter bag is prepared by adopting the above method.

[0022] Furthermore, in the catalytic filter bag, the weight ratio of CoO, MnO, In2O3 and TiO2 in the CoO-MnO-In2O3@TiO2 catalyst is 0.1-5:0.1-5:0.1-5:5-15; the loading capacity of the catalytic filter bag is 300-600 g / m 2 ;

[0023] Furthermore: the mass ratio of CoO, MnO, In2O3 and TiO2 in the CoO-MnO-In2O3@TiO2 catalyst is 0.5~3.5:1.0~2.5:0.5~2.0:8~12.

[0024] In the technical solution of the present invention, the catalyst prepared by the method is used for removing fine particles from incineration flue gas and for catalytic oxidation of VOCs.

[0025] Beneficial effects of the invention: The invention provides a catalytic filter bag for removing fine particles from incineration flue gas and catalytic oxidation of VOCs, and a preparation method and application thereof. The general formula is CoO-MnO-In2O3@TiO2 core-shell structure VOCs catalytic oxidation catalyst composition has a higher VOCs catalytic oxidation removal efficiency at a lower temperature; the TiO2 shell layer prevents the poisoning of SO2 and water vapor on the catalyst active component CoO-MnO-In2O3, thereby improving the sulfur resistance of the oxidation catalyst; at the same time, the thermal stability of the catalyst active component is improved, and the catalyst life is extended; ball milling technology is used to make the catalyst and adhesive mix more evenly and the particle size smaller, and the formed catalyst sol slurry has stronger adhesion to the filter bag matrix and a higher loading rate; automatic spraying technology is used to improve the production efficiency of catalytic filter bags. DETAILED DESCRIPTION

[0026] The present invention will be further described below through specific examples, and all examples are operated completely according to the steps described in the present invention.

[0027] Example 1

[0028] Treatment of filter bag substrate

[0029] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0030] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0031] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 49.0g Co(NO3)2.6H2O (98.0%), 125.0g Mn(NO3)2.4H2O (97.5%) and 14.4gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate (the molar ratio of sodium hydroxide to ammonium carbonate was 1:1) at 60°C, the pH value was adjusted to 8.5, and after the addition, stirring was continued for 20 hours for nucleation and crystallization, and then allowed to stand, filtered, washed until neutral, dried at 120°C for 5 hours, calcined at 550°C for 8 hours, cooled naturally to room temperature, ground into 10μm powder, and a CoO-MnO-In2O3 ternary metal oxide composite was obtained;

[0032] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50°C, and ultrasonically dispersed for 30 minutes. After the dispersion was complete, 170 g of TiCl4 was slowly dropped into it under stirring, and then the temperature was raised to 80°C and stirred for 2 hours to form a gel; the obtained gel was dried at 120°C for 20 hours, and then placed in a muffle furnace, calcined at 420°C for 3 hours, and then calcined at 650°C for 6 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 1.0:2.0:1.0:9.5 and having a core-shell structure.

[0033] (3) Preparation of substrate-supported catalyst slurry

[0034] Weigh 10.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 8.5g of SB powder, and 0.2g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 6.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.99%.

[0035] (4) Preparation of catalytic filter material

[0036] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 4 hours, sprayed twice, and calcined at 220°C for 4 hours to obtain a catalyst loading of 438 g / m 2 Catalytic filter material 1.

[0037] Example 2

[0038] Treatment of filter bag substrate

[0039] Place the polyphenylene sulfide (PPS) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0040] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0041] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask, and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 73.5g Co(NO3)2.6H2O (98.0%), 62.5g Mn(NO3)2.4H2O (97.5%) and 21.6gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate (the molar ratio of sodium hydroxide to ammonium carbonate was 1:1) at 60°C, the pH value was adjusted to 9.0, and after the addition, stirring was continued for 18 hours for nucleation and crystallization, and then the mixture was allowed to stand, filtered, and washed until neutral, dried at 140°C for 6 hours, calcined at 580°C for 8 hours, cooled naturally to room temperature, and ground into 10μm powder to obtain a CoO-MnO-In2O3 ternary metal oxide composite;

[0042] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50° C., and ultrasonically dispersed for 30 minutes. After it was completely dispersed, 170 g of TiCl4 was slowly dropped under stirring, and then the temperature was raised to 80° C. and stirred for 2 hours to form a gel; the obtained gel was dried at 130° C. for 20 hours, and then placed in a muffle furnace, calcined at 420° C. for 3 hours, and then calcined at 650° C. for 8 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 1.5:1.0:1.5:9.5 and having a core-shell structure.

[0043] (3) Preparation of substrate-supported catalyst slurry

[0044] Weigh 6.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 7.5g of SB powder, and 0.2g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 6.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 4.52%.

[0045] (4) Preparation of catalytic filter material

[0046] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 6 hours, sprayed three times, and calcined at 200°C for 4 hours to obtain a catalyst with a loading of 375 g / m 2 Catalytic filter material 2.

[0047] Example 3

[0048] Treatment of filter bag substrate

[0049] Place the polyimide (P84) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0050] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0051] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask, and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 89.1g Co(NO3)2.6H2O (98.0%), 90.9g Mn(NO3)2.4H2O (97.5%) and 10.4gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate (the molar ratio of sodium hydroxide to ammonium carbonate was 1:1) at 60°C, the pH value was adjusted to 9.0, and after the addition, stirring was continued for 18 hours for nucleation and crystallization, and then allowed to stand, filtered, washed until neutral, dried at 130°C for 4 hours, calcined at 650°C for 5 hours, cooled naturally to room temperature, ground into 10μm powder, and a CoO-MnO-In2O3 ternary metal oxide composite was obtained;

[0052] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50° C., and ultrasonically dispersed for 30 minutes. After it was completely dispersed, 170 g of TiCl4 was slowly dropped under stirring, and then the temperature was raised to 80° C. and stirred for 2 hours to form a gel; the obtained gel was dried at 130° C. for 20 hours, and then placed in a muffle furnace, calcined at 420° C. for 3 hours, and then calcined at 650° C. for 8 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 2.5:2.0:1.0:9.5 and having a core-shell structure.

[0053] (3) Preparation of substrate-supported catalyst slurry

[0054] Weigh 12.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 10.5g of SB powder, and 0.3g of Tianqing powder, grind and mix them in a ball mill for 4 hours, mix and grind them thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 10.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 6.95%.

[0055] (4) Preparation of catalytic filter material

[0056] The catalyst slurry was coated on the polyimide (P84) filter bag substrate treated in step (1) by an automatic sprayer, dried at 110°C for 5 hours, sprayed repeatedly 5 times, and calcined at 180°C for 8 hours to obtain a catalyst loading of 516 g / m 2 Catalytic filter material 3.

[0057] Example 4

[0058] Treatment of filter bag substrate

[0059] The polytetrafluoroethylene (PTFE) filter bag material was placed in a beaker, and a nitric acid solution with a concentration of 20% (mass concentration) was added. The material was immersed in the solution at 45°C for 2 hours, and then washed with deionized water and dried in a forced air drying oven at 105°C for 2 hours to obtain the pretreated filter bag substrate.

[0060] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0061] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask, and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 98.0g Co(NO3)2.6H2O (98.0%), 41.7g Mn(NO3)2.4H2O (97.5%) and 19.2gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate at 60°C, and the pH value was adjusted to 9.5. After the addition was completed, stirring was continued for 20 hours for nucleation and crystallization, and then cooled, filtered, washed to neutrality, dried at 150°C for 4 hours, calcined at 620°C for 8 hours, cooled naturally to room temperature, and ground into 10μm powder to obtain a CoO-MnO-In2O3 ternary metal oxide composite;

[0062] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50° C., and ultrasonically dispersed for 30 minutes. After it was completely dispersed, 170 g of TiCl4 was slowly dropped under stirring, and then the temperature was raised to 80° C. and stirred for 2 hours to form a gel; the obtained gel was dried at 120° C. for 20 hours, and then placed in a muffle furnace, calcined at 420° C. for 3 hours, and then calcined at 650° C. for 5 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 3.0:1.0:2.0:9.5 and having a core-shell structure.

[0063] (3) Preparation of substrate-supported catalyst slurry

[0064] Weigh 4.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 4.5g of SB powder, and 0.3g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 5.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 2.95%.

[0065] (4) Preparation of catalytic filter material

[0066] The catalyst slurry was coated on the polytetrafluoroethylene (PTFE) filter bag substrate treated in step (1) by an automatic sprayer, dried at 120°C for 3 hours, sprayed 3 times, and calcined at 220°C for 5 hours to obtain a catalyst loading of 531 g / m 2 Catalytic filter material 4.

[0067] Example 5

[0068] Treatment of filter bag substrate

[0069] Place the polyphenylene sulfide (PPS) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0070] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0071] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask, and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 98.0g Co(NO3)2.6H2O (98.0%), 89.3g Mn(NO3)2.4H2O (97.5%) and 12.3gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate at 60°C, and the pH value was adjusted to 9.0. After the addition was completed, stirring was continued for 18 hours for nucleation and crystallization, and then cooled, filtered, washed to neutrality, dried at 135°C for 8 hours, calcined at 650°C for 8 hours, cooled naturally to room temperature, and ground into 10μm powder to obtain a CoO-MnO-In2O3 ternary metal oxide composite;

[0072] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50°C, and ultrasonically dispersed for 30 minutes. After it was completely dispersed, 170 g of TiCl4 was slowly dropped under stirring, and then the temperature was raised to 80°C and stirred for 2 hours to form a gel; the obtained gel was dried at 120°C for 18 hours, and then placed in a muffle furnace, calcined at 420°C for 4 hours, and then calcined at 650°C for 6 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 3.5:2.0:1.5:9.5 and having a core-shell structure.

[0073] (3) Preparation of substrate-supported catalyst slurry

[0074] Weigh 13.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 13.5g of SB powder, and 0.3g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 20μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 20.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 7.85%.

[0075] (4) Preparation of catalytic filter material

[0076] The catalyst slurry was coated on the polyphenylene sulfide (PPS) filter bag substrate treated in step (1) by an automatic sprayer, dried at 120°C for 5 hours, sprayed 4 times, and calcined at 190°C for 5 hours to obtain a catalyst loading of 506 g / m 2 Catalytic filter material 5.

[0077] Example 6

[0078] Treatment of filter bag substrate

[0079] Place the polyimide (P84) filter bag material in a beaker, add a nitric acid solution with a concentration of 20% (mass concentration), immerse it at 45°C for 2 hours, then wash it with deionized water, place it in a forced air drying oven at 105°C for 2 hours, and obtain the pretreated filter bag matrix.

[0080] (1) Preparation of CoO-MnO-In2O3@TiO2 core-shell structure catalyst

[0081] Weigh 140g dodecylamine, 1000mL n-butanol (mass percentage concentration ≥ 99.5) and 1500mL deionized water, add them into a three-necked flask, and start stirring; dissolve dodecylamine completely in n-butanol to obtain a microemulsion liquid; weigh 65.4g Co(NO3)2.6H2O (98.0%), 83.3g Mn(NO3)2.4H2O (97.5%) and 19.2gIn(NO3)3.H2O (99.5%) were added into a three-necked flask; when the solid was completely dissolved, the mixed solution was added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate at 60°C, and the pH value was adjusted to 9.5. After the addition was completed, stirring was continued for 20 hours for nucleation and crystallization, and then cooled, filtered, washed until neutral, dried at 125°C for 8 hours, calcined at 580°C for 10 hours, cooled naturally to room temperature, and ground into 10μm powder to obtain a CoO-MnO-In2O3 ternary metal oxide composite;

[0082] (2) 500 mL of 60% ethanol solution was measured and placed in a beaker, and 30 g of the CoO-MnO-In2O3 ternary metal oxide composition prepared in the above steps was added under stirring at 50° C., and ultrasonically dispersed for 30 minutes. After it was completely dispersed, 170 g of TiCl4 was slowly dropped into it under stirring, and then the temperature was raised to 80° C. and stirred for 2 hours to form a gel; the obtained gel was dried at 105° C. for 20 hours, and then placed in a muffle furnace, calcined at 420° C. for 3 hours, and then calcined at 650° C. for 7 hours to obtain a CoO-MnO-In2O3@TiO2 catalyst composition with a weight ratio of CoO, MnO, In2O3 and TiO2 of 1.0:1.0:1.0:9.5 and having a core-shell structure.

[0083] (3) Preparation of substrate-supported catalyst slurry

[0084] Weigh 8.5g of CoO-MnO-In2O3@TiO2 catalyst composition, 9.5g of SB powder, and 0.3g of Tianqing powder, grind and mix them in a ball mill for 4 hours, mix and grind them thoroughly, and the particle size reaches 15μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 15.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.48%.

[0085] (4) Preparation of catalytic filter material

[0086] The catalyst slurry was coated on the polyimide (P84) filter bag substrate treated in step (1) by an automatic sprayer, dried at 120°C for 4 hours, sprayed three times, and calcined at 185°C for 6 hours to obtain a catalyst loading of 378 g / m2 Catalytic filter material 6.

[0087] Comparative Example 1

[0088] (1) The treatment of the filter bag substrate is the same as in Example 1;

[0089] (2) Preparation of CoO-MnO-In2O3-TiO2 quaternary metal oxide catalyst

[0090] 1) Weigh 140 g of dodecylamine, 1000 mL of n-butanol (mass percentage concentration ≥ 99.5) and 1500 mL of deionized water, add them into a three-necked flask, and start stirring; dissolve the dodecylamine completely in the n-butanol to obtain a microemulsion liquid;

[0091] 2) Weigh 49.0g Co(NO3)2.6H2O (98.0%), 125.0g Mn(NO3)2.4H2O (97.5%) and 14.4gIn(NO3)3.H2O (99.5%) and 170.0gTiCl4 (99.5%) are added into a three-necked flask; when the solid is completely dissolved, the mixed solution is added dropwise into a mixed solution of 5% sodium hydroxide and sodium carbonate at 60°C, and the pH value is adjusted to 9.5. After the addition is completed, stirring is continued for 20 hours for nucleation and crystallization, and then cooled, filtered, washed to neutrality, dried at 125°C for 6 hours, calcined at 580°C for 10 hours, naturally cooled to room temperature, ground into 10μm powder, and a CoO-MnO-In2O3-TiO2 quaternary metal oxide composition with a weight ratio of CoO:MnO:In2O3:TiO2=1.0:2.0:1.0:9.5 is obtained.

[0092] (3) Preparation of substrate-supported catalyst slurry

[0093] Weigh 10.5g of CoO-MnO-In2O3-TiO2 quaternary metal oxide composition, 8.5g of SB powder, and 0.2g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 6.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.99%.

[0094] (4) Preparation of catalytic filter material The same as step (4) of Example 1 was used to obtain a catalyst with a loading of 487 g / m 2 Comparative catalytic filter material 1.

[0095] Comparative Example 2

[0096] (1) Treatment of the filter bag substrate and (2) preparation of the CoO-MnO-In2O3@TiO2 core-shell structure catalyst are the same as steps (1) and (2) of Example 4, respectively.

[0097] (3) Preparation of substrate-supported catalyst slurry

[0098] Weigh 4.5g of CoO-MnO-In2O3@TiO2 catalyst composition and 4.8g of carboxymethyl cellulose, grind and mix in a ball mill for 4 hours, mix and grind thoroughly, and the particle size reaches 10μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 5.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 2.95%.

[0099] (4) Preparation of catalytic filter material The same as step (4) of step 4 was carried out to obtain a catalyst with a loading of 241 g / m 2 Comparative catalytic filter material 2.

[0100] Comparative Example 3

[0101] (1) Treatment of the filter bag substrate and (2) preparation of the CoO-MnO-In2O3@TiO2 core-shell structure catalyst are the same as steps (1) and (2) of Example 6, respectively.

[0102] (3) Preparation of substrate-supported catalyst slurry

[0103] Weigh 8.5g of CoO-MnO-In2O3@TiO2 catalyst composition and 9.8g of Tianqing powder, grind and mix them in a ball mill for 4 hours, mix and grind them thoroughly, and the particle size reaches 15μm; add 300g of deionized water to a 1000mL beaker, add the above ball-milled mixture powder while stirring, and then slowly add 15.5g of 10% nitric acid, ultrasonically homogenize for 8 hours, and obtain a matrix-loaded catalyst sol slurry with a mass concentration of 5.48%.

[0104] (4) Preparation of catalytic filter material The same as step (4) of step 6 was carried out to obtain a catalyst with a loading of 226 g / m 2 Comparative catalytic filter material 3.

[0105] Performance testing:

[0106] The performance evaluation of the catalytic filter bag for removing fine particles from incineration flue gas and catalytic oxidation of VOCs prepared in the above-mentioned embodiments and comparative examples is carried out by putting the catalytic filter bag on the sleeve. The evaluation conditions are: the concentration of styrene in the flue gas is 800 mg / m 3 , O2 volume fraction is 8%, water vapor content is 15% (volume ratio), SO2 concentration is 450mg / m3 , dust concentration 1500mg / m 3 , filtration wind speed 0.75m / min (filter bag size). The performance of the catalytic filter bag was evaluated by the changes in the inlet and outlet styrene and dust concentrations. The results are shown in Table 1.

[0107] Table 1 Evaluation of catalytic filter bag denitrification, dedioxin and dust removal performance

[0108] Group VOC removal rate, % Dust removal efficiency, % Example 1 93.1 99.1 Example 2 92.7 98.8 Example 3 92.6 98.6 Example 4 94.2 98.4 Example 5 93.2 98.5 Example 6 94.7 99.2 Comparative Example 1 82.2 97.4 Comparative Example 2 78.5 93.1 Comparative Example 3 72.8 92.6

[0109] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A method for preparing a catalytic filter bag, characterized in that: The preparation method comprises the following steps: (1) dodecylamine and alcohol are added to deionized water to form a microemulsion liquid, cobalt salt, manganese salt and indium salt are added to the microemulsion liquid and mixed; after mixing, the mixture is slowly added to a precipitant, and then stirred for 12 to 20 hours. The obtained crystals are sequentially subjected to standing, centrifugation, washing, drying, roasting and grinding to obtain a CoO-MnO-In2O3 ternary metal oxide composition with a particle size of 5 to 15 μm; (2) Adding a CoO-MnO-In2O3 ternary metal oxide composition to an alcohol aqueous solution and dispersing it uniformly, then adding TiCl4 and reacting it at a temperature of 75 to 85°C for 1.5 to 2 hours, then drying the gel and calcining it to obtain a CoO-MnO-In2O3@TiO2 catalyst composition having a core-shell structure; (3) Grinding and mixing CoO-MnO-In2O3@TiO2 and the additive, and then sequentially adding water and nitric acid and mixing, to obtain a matrix-supported catalyst sol slurry; (4) The substrate-loaded catalyst sol slurry is sprayed onto the pretreated filter bag carrier and then dried and calcined in sequence to obtain a catalytic filter material.

2. The preparation method according to claim 1, characterized in that: The alcohol in step (1) is n-butanol, and the mass ratio of dodecylamine, n-butanol and deionized water in the microemulsion is 1-5:8-12:10-20; The mass ratio of the microemulsion to the metal salt is 20-30:1-5, and the metal salt is cobalt salt, manganese salt and indium salt.

3. The preparation method according to claim 1, characterized in that: The drying temperature in step (1) is 120-150° C., the drying time is 4-8 hours, the roasting temperature is 550-650° C., and the roasting time is 4-10 hours; the precipitant is a mixed solution of sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to ammonium carbonate is 1-3:1-3.

4. The preparation method according to claim 1, characterized in that: The alcohol aqueous solution described in step (2) is a 40-60% ethanol solution; the drying temperature is 100-130° C., and the drying time is 12-20 hours; the roasting temperature is first roasting at a temperature of 400-450° C. for 2-4 hours, and then roasting at a temperature of 630-680° C. for 4-8 hours.

5. The preparation method according to claim 1, characterized in that: The mass concentration of the substrate-supported catalyst sol slurry in step (3) is 1 to 10%.

6. The preparation method according to claim 1, characterized in that: The auxiliary agent described in step (3) is a mass ratio of 3 to 15: A combination of 0.1 to 1 SB powder and carboxymethyl cellulose or a combination of SB powder and Tianqing powder, wherein the mass ratio of the auxiliary agent and the CoO-MnO-In2O3@TiO2 catalyst composition is 1 to 3:1 to 3.

7. The preparation method according to claim 1, characterized in that: The filter bag pretreatment method in step (4) is to soak the filter bag in 10-30% nitric acid at a temperature of 40-50°C for 1-3 hours, then wash and dry the filter bag at 100-110°C for 1-3 hours; the filter bag is made of tetrafluoroethylene PTFE, polyphenylene sulfide PPS or polyimide P84. In step (4), the drying temperature is 105-120° C. for 3-6 hours, and the calcination temperature is 180-220° C. for 1-8 hours.

8. A catalytic filter bag, characterized in that: The invention discloses a novel cellulose acetate resin having a slurry containing cellulose fibers. The cellulose acetate resin is prepared by the method according to any one of claims 1 to 6.

9. The filter bag according to claim 7, characterized in that: The weight ratio of CoO, MnO, In2O3 and TiO2 in the CoO-MnO-In2O3@TiO2 catalyst is 0.1-5:0.1-5:0.1-5:5-15; the loading amount of the catalytic filter bag is 300-600 g / m 2 ; Preferably, the mass ratio of CoO, MnO, In2O3 and TiO2 in the CoO-MnO-In2O3@TiO2 catalyst is 0.5-3.5:1.0-2.5:0.5-2.0:8-12.

10. Use of the catalyst prepared by the method according to claim 1 for removing fine particles from incineration flue gas and in catalytic oxidation of VOCs.

Citation Information

Patent Citations

  • Catalytic fibers capable of catalytically removing gaseous organic pollutants and their preparation methods, catalytic filter bags and baghouse dust collectors

    CN107321348B

  • Plasma synergistic catalyst oxidation degradation VOCs dedusting filter cloth

    CN109954403A

  • Method for deep purifying organic toxicant and waste water by photocatalysis-oxidation and preparation method for used photocatalysis material

    CN101838078A

  • Low-temperature SCR denitration catalyst with titanium-based core-shell structure and preparation method of catalyst

    CN104190408A

  • Graphene-loaded titanium-based core-shell-structured low-temperature SCR sulfur-resisting catalyst and preparation method thereof

    CN104190409A